2019
DOI: 10.3389/fgene.2019.00069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficiencies of Non-invasive Prenatal Testing, Karyotyping, and Chromosomal Micro-Array for Diagnosing Fetal Chromosomal Anomalies in the Second and Third Trimesters

Abstract: In this study, we aimed to compare the efficiency of non-invasive prenatal testing (NIPT), karyotyping, and chromosomal micro-array (CMA) for the diagnosis of fetal chromosomal anomalies in the second and third trimesters. Pregnant women, who underwent amniocenteses for prenatal genetic diagnoses during their middle and late trimesters, were recruited at the Prenatal Diagnosis Center of Taizhou City. Maternal blood was separated for NIPT, and amniotic fluid cells were cultured for karyotyping and CMA. The diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(42 reference statements)
0
6
0
5
Order By: Relevance
“…A total of 16 included studies reported cfDNA results for Klinefelter Syndrome (47,XXY). 30,[32][33][34][35][36][37][38][39]41,44,46,[48][49][50] This represented 11,248 cell-free DNA tests with 62 confirmed affected pregnancies, 10 false positive tests and 10 false negative tests (Supplemental Table 2). The pooled estimated sensitivity was 100% (95%CI 99.6%-100%) and specificity was 100% (95%CI 99.9%-100%) (Table 2).…”
Section: Xxymentioning
confidence: 99%
“…A total of 16 included studies reported cfDNA results for Klinefelter Syndrome (47,XXY). 30,[32][33][34][35][36][37][38][39]41,44,46,[48][49][50] This represented 11,248 cell-free DNA tests with 62 confirmed affected pregnancies, 10 false positive tests and 10 false negative tests (Supplemental Table 2). The pooled estimated sensitivity was 100% (95%CI 99.6%-100%) and specificity was 100% (95%CI 99.9%-100%) (Table 2).…”
Section: Xxymentioning
confidence: 99%
“…Since the first application of NIPT in the prenatal screening of fetal CNVs reported in 2011 (Peters et al., 2011), many institutions have studied the utility of using NIPT to detect CNVs (Pös et al., 2019; Zhu et al., 2019). However, because of the placental origin of fetal DNA owing to the low sequencing depth or low production of fetal DNA template, NIPT yields false‐negative and false‐positive results during the screening of CNVs (Xu et al., 2016; Yin et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…De forma geral, o de segunda detectou mais anormalidades (2,68%) do que o de primeira (0,90%), sendo a taxa de triagem positiva variante com a geração escolhida. (12) Como limitações associadas ao exame, encontrou-se que uma fração de DNA fetal se origina da apoptose do sinciciotrofoblasto, (7,16) podendo ocorrer falsos negativos (FN) e positivos pelo mosaico da placenta (prevalência desconhecida). (16) 4.2 EFICÁCIA DO NIPT Um estudo Chinês com 17.428 gestações relatou 202 amostras NIPT positivas, sendo que 160 dessas foram encaminhadas à amniocentese com confirmação de 1,16% após o procedimento, 0,07% de falso positivo (FP) e 0% FN.…”
Section: A Realização Do Exameunclassified
“…(12) Como limitações associadas ao exame, encontrou-se que uma fração de DNA fetal se origina da apoptose do sinciciotrofoblasto, (7,16) podendo ocorrer falsos negativos (FN) e positivos pelo mosaico da placenta (prevalência desconhecida). (16) 4.2 EFICÁCIA DO NIPT Um estudo Chinês com 17.428 gestações relatou 202 amostras NIPT positivas, sendo que 160 dessas foram encaminhadas à amniocentese com confirmação de 1,16% após o procedimento, 0,07% de falso positivo (FP) e 0% FN. O VP foi de 84,38% para trissomia 21; 61,54% para a trissomia 18; 52,94% para as anormalidades autossômicas; 38,46% para as anormalidades cromossômicas sexuais; e de 33,33% para a trissomia 12.…”
Section: A Realização Do Exameunclassified